IN VIVO ANTIDIABETIC POTENTIAL OF CYCLEA PELTATA IN STREPTOZOTOCIN‑INDUCED‑DIABETIC RATS - Ms, Sangeetha; S, Priyanga; S, Hemmalakshmi; K, Devaki (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Diabetes is one of the most common metabolic disorders in worldwide. Diabetes mellitus is a disorder of carbohydrate metabolism in which sugars in the body are not oxidized to produce energy due to lack of the pancreatic hormone, insulin. This study was undertaken to find out the antioxidant and antidiabetic potential of ethanolic root extract of Cyclea peltata. Methods: The ethanolic root extract of C. peltata was administered to control and the experimental rats for 30 days. After the experimental period, the animals were sacrificed and the serum, tissue samples were used for the determination of blood glucose level, protein, urea, creatinine, liver marker enzymes, antioxidant enzymes, lipid profile, protein, lipid peroxidation and histopathological examination. Results: The results of this study supports that the ethanolic root extract of C. peltata shows better antioxidant potential through which it exert antidiabetic potential. Histopathology results also support the protective effect of C. peltata against streptozotocin induced diabetes. Conclusion: The results scientifically confirm that the C. peltata can be used to treat various disorders caused by free radicals and other chemical substances due to the presence of secondary metabolites that exert antioxidant and antidiabetic action. Keywords: Antidiabetic, Antioxidants, Cyclea peltata, Lipid peroxidation.